(In)equality in Education and Economic Development. (11th September 2014) - Sauer, Petra; Zagler, Martin
Abstract : This paper investigates the relationship between the level and the distribution of education and economic development. We contribute to the literature by introducing an interaction term between the education Gini coefficient and average years of schooling. In a dynamic panel over 55 years and 134 countries we provide, on the one hand, strong evidence that more schooling is good for growth, but the coefficient is variable and substantially declining in the degree of inequality. The aggregate benefit to education thus depends on a country's position in the education distribution. On the other hand, we find a slight transitional increase in education inequality to be beneficial at a very low average level of schooling, but detrimental for growth at a relatively high average level. Allowing for the macroeconomic return to education to be heterogeneous with respect to the degree of inequality is therefore paramount in understanding the relationship between education and development.